Exercise Echocardiography following Septal Myectomy for Hypertrophic Obstructive Cardiomyopathy - Novén, Johan; Stagmo, Martin; Wierup, Per; Nozohoor, Shahab; Bjursten, Henrik; Sjögren, Johan; Zindovic, Igor; Ragnarsson, Sigurdur (The Thoracic and Cardiovascular Surgeon, 2020)
Objectives To investigate outcome after septal myectomy and to evaluate long-term hemodynamics with exercise echocardiography.Methods This study included 40 consecutive patients operated with septal myectomy for hypertrophic obstructive cardiomyopathy from January 1998 to August 2017 at Skane University Hospital, Lund, Sweden. Perioperative clinical data and echocardiography measurements were reviewed retrospectively. Patients (n = 36) who were alive and living in Sweden were invited for exercise echocardiography to evaluate exercise capacity and hemodynamics, of whom 19 patients performed exercise echocardiography.Results Overall survival was 100% at 1 year and 96% at 5 years following surgery. Preoperative median resting peak LVOT (left ventricular outflow tract) gradient was 80 mm Hg. Septum thickness was reduced from 22 ± 4 mm preoperatively to 16 ± 3 mm postoperatively (p < 0.001). During exercise echocardiography, the peak LVOT gradient was 8 mm Hg at rest, and increased to 13 mm Hg during exercise echocardiography (p = 0.002). None of the patients had dynamic LVOT obstruction during exercise echocardiography, and there was no clinically significant systolic anterior motion or severe mitral insufficiency during exercise.Conclusions Long-term survival following septal myectomy is very good. At long-term follow-up, LVOT gradients were low and exercise echocardiography demonstrated good hemodynamics.
Keywords: hypertrophic obstructive cardiomyopathy; septal myectomy; exercise echocardiography